Study to estimate impact of sudden lockdown due to COVID-19 pandemic at the household level: findings of cross-sectional study in Tamil Nadu - Srinivas, Vani; Murugan, V. (International Journal Of Community Medicine And Public Health, 2023)
Background: In response to contain the spread of coronavirus disease 2019 (COVID-19) in India, the entire country was declared to be under lockdown from the midnight of 24 March 2020. In this study, we determined the economic impact and availability of health services during sudden lockdown. Methods: A cross sectional study was done in rural and urban health and training centres attached to rural medical college of Chengalpattu district of Tamil Nadu. Sample size was 424. Study participants were out patients, seeking health care services. Data was collected by trained medical social workers (MSW), using field tested semi-structured questionnaire. Percentages were calculated and for assessing difference between proportions, Pearson’s chi-square test was used as a test of significance. Results: Out of 424 study participants, 223 (52.6%) were male and mean age of participants was 44 years. Socio economically, majority of them belonged to lower and lower middle-class families. 297 (70%) of households reported to have financial loss and 71.2% reported difference due to lockdown. In univariant analysis, the significant risk factors for difference in income were found to be type of house (0.029), loss of job (0.0001), loss of wages (0.0001), having bank loan (0.019) and issues in managing household expenses (0.0001), per capita income (0.008), farming business (0.018) and household with members having non-communicable diseases (0.013). Conclusions: Lockdown has huge economic cost. Underprivileged households were economically impacted. Most of the essential health services were available and accessible to the household even during the strict lockdown.